International communication of technological knowledge: an empirical study of Taiwan's manufacturing firms. (28th August 2007) - Lin, Bou-Wen; Berg, Daniel
The objective of this article is to develop an integrative model of international technology/knowledge transfer (TT/KT). One hundred and eighty-one manufacturing firms in Taiwan were surveyed. The model from a communication perspective focuses on the communication process of TT/KT at the work group and firm level. The model embraces four antecedent variables - climate of collaboration, autonomy of teamwork, technology transferability and competence gaps - to explain communication quality and TT/KT success. Communication quality at the inter-firm and inter-group levels plays a mediating role between those four antecedent variables and TT/KT effectiveness. Empirical evidence supports the communication-based TT/KT model and hypotheses derived. Inter-firm technology or knowledge transfer should be seen as a communication process involving two courses of information flow - workgroup and inter-firm communications. Each course has its antecedents that affect its communication quality. Managerial implications and future research directions are also discussed.